Penerapan Fungsi Perencanaan (Planning) dalam Pembinaan Akhlak Santri di Pondok Pesantren Al-Mukhtariyah Ambai - Mauliyani Mauliyani; Ivan Sunata (Institut Agama Islam Negeri Kerinci, 2024)
This research aims to find out how the Planning Function is implemented in the Moral Development of Santri at the Al-Mukhtariyah Ambai Islamic Boarding School. The results of the research show that the moral condition of the students at the Muktariah Ambai Islamic boarding school is generally good. The implementation of the planning function has been implemented well, starting with a vision and mission that produces a generation of students who are visionary, professional and have the skills to face global challenges based on faith and piety. As well as creating generations who excel and are clever in various fields as well as a young generation who have akhlatul kharimah